Progress in heterocyclic chemistry : Vol. 26 - Gribble, Gordon W.; Joule, J. A. (John Arthur) (Burlington : Elsevier Science, 2014)
This is the 26th annual volume of Progress in Heterocyclic Chemistry and covers the literature published during 2013 on most of the important heterocyclic ring systems. This volume opens with two specialized reviews, not restricted to work published in 2013: 'Recent Developments in the Synthesis of Cyclic Guanidine Alkaloids' written by Matthew G. Donahue, and 'Heterocyclic chemistry: a complete toolbox for nanostructured carbon materials' written by Luisa Lascialfari, Stefano Fedeli, and Stefano Cicchi. The remaining chapters examine the 2013 literature on the common heterocycles in order of increasing ring size and the heteroatoms present.
Includes bibliographical references at the end of each chapters and index.
Keywords: Heterocyclic chemistry; Heterocyclic compounds; SCIENCE -- Chemistry -- Organic; Heterocyclic chemistry; Heterocyclic compounds; Electronic books